An Empirical Study of the Impact of Nonlinear Shipping and Handling Fees on Purchase Incidence and Expenditure Decisions - Lewis, Michael; Singh, Vishal; Fay, Scott (Marketing Science, 2006)
Shipping-fee schedules are an important but underresearched element of the marketing mix for direct marketers. This paper provides an empirical study on the impact of shipping and handling charges on consumer-purchasing behavior. Using a database from an online retailer that has experimented with a wide variety of shipping-fee schedules, we investigate the impact of shipping charges on order incidence and order size. We use an ordered probability model that is generalized to account for the effects of nonlinear and discontinuous shipping fees on purchasing decisions, and to accommodate heterogeneity in response parameters. Results show that consumers are very sensitive to shipping charges and that shipping fees influence order incidence and basket size. Promotions such as free shipping and free shipping for orders that exceed some size threshold are found to be very effective in generating additional sales. However, the lost revenues from shipping and the lack of response by several segments are substantial enough to render such promotions unprofitable to the retailer. Heterogeneity across consumers also suggests interesting opportunities for the retailer to customize the shipping and other marketing-mix promotion offerings.